FEATURES OF THE INTERNAL AUDIT OF MATERIAL VALUES IN HIGHER EDUCATION INSTITUTIONS - E., Sindarov Sh. (Research Parks Publishers, 2023)
In this article, the auditing methods and procedures used in the internal audit of tangible assets in higher education institutions, in particular, the content of the inventory method used in this process, the characteristics of the inventory method, and the relevance of conducting research in this field are revealed. In the